Enhancing tissue repair in annulus fibrosus defects of the intervertebral disc: analysis of a bio-integrative annulus implant in an in-vivo ovine model - Hegewald, Aldemar Andres; Tsagogiorgas, Charalambos; Shenegelegn Mern, Demissew (Journal of tissue engineering and regenerative medicine, 2015)
Annulus fibrosus repair techniques for the intervertebral disc (IVD) address the unsolved problem of reherniation after IVD herniation and might facilitate the development of nucleus pulposus replacement techniques for IVD diseases. This study investigates the suitability of a bio-integrative annulus implant.Standardized box defects were applied to the annulus L3/4 and L4/5 of 16 sheep, followed by randomized insertion of the textile polyglycolic acid/polyvinylidene fluoride annulus implant in one of the defects. Explantation was conducted after 2, 6 and 12 weeks, followed by provocative pressure testing and histological analysis. At 2 weeks’ follow-up, all specimens of the control defect group demonstrated uncontained herniated nucleus pulposus tissue in the annulus defects. For the treated specimens, the annulus implant consistently provided an effective barrier for herniating nucleus pulposus tissue, with no implant dislocation at all time-points. After 2 weeks, a homogeneous cell infiltration of the annulus implant was observed, leading to a progressive directional matrix build-up. Repair tissue thickness was significantly stronger with the annulus implant at all follow-ups (p < 0.01). No pronounced foreign body reaction and no difference in the amount of supra-annular scar tissue over the defect sites were observed. The implantation procedure inflicted annulus damage adjacent to the defect. At later time-points, however, no difference in comparison with the control defect group was evident. The investigated biointegrative annulus implant showed promising results with regard to biointegration, enhancement of repair tissue and function as a mechanical barrier in an ovine model.